Komodifikasi Masyarakat Tontonan dalam Demo Tolak RKUHP dan Revisi UU KPK - Khairul Syafuddin (Komuniti: Jurnal Komunikasi dan Teknologi Informasi, 2019)
Indonesian students on 23 September 2019 then showed forms of opposition to the RKUHP and the Revision of the KPK Law. They show this through the appeals written on the poster during the demonstration. One of the locations that became a meeting point in Gejayan, which is famous for #gejayanmemmon. The purpose of this study is to study how members of the media publish and carry out the commodification of the evaluation measures. The method used in this research is content analysis. Researchers collected some of the content produced by students and posted on the online news web. from the content, then the study conducted an analysis using public spectacle theory from Guy Debord and the commodification of Vincent Mosco. The results of this study indicate that the media are taking advantage of this action by making their action a spectacle for the public. That way the media can get success from the demonstration with a fairly low economic capital, because all the content of the demonstration that has been done has spread through social media. Enough media to sample the content available on social media.